Association of PCSK9 g.24382G > A with Increased Homocysteine Level among Bidayuh Ethnic Group in Sarawak Population - Mohd Aminudin, Mustapha; Sim, Sai-Peng; Helmy, Hazmi; Goh, Maybelline Boon Ling (Japan International Cultural Exchange Foundation (JICEF), 2019)
Objective: To determine the polymorphic allele and genotype frequencies of Proprotein Convertase Subtilisin/Kexin type 9 PCSK9 g.24382G > A. It aimed to elucidate the association of the polymorphic allele and genotypes with clinical profiles such as total cholesterol (TC), high- density lipoprotein (HDL), low- density lipoprotein (LDL) and homocysteine level in the Bidayuh ethnic group in Sarawak. Material and Methods: One hundred and thirty-nine (139) individuals from the Bidayuh ethnic group in Sarawak participated as study subjects. The Allele Specific PCR (AS-PCR) was used in the genotyping of PCSK9 g.24382G > A to detect the selected SNPs variant (Polymorphisms). Association of genotype frequencies with clinical profile was calculated using One Way ANOVA. As for the association of allele frequencies with clinical profile, Independent Sample T test was used. Results: Heterozygous genotype was statistically higher in normal level of total cholesterol level, LDL and homocysteine level whereas high level of total cholesterol and HDL ratio was statistically higher in variant genotype compared to homozygous genotype (p < 0.05). Heterozygous and variant genotypes of PCSK9 g.24382G > A show that it is significantly associated with high homocysteine level, F (1,137) = 5.018 (p = 0.027). Conclusion: Our results showed that the genetic diversity of PCSK9 gene influences the susceptibility to increased level of homocysteine in the Malaysian population and also support the involvement of LDLR mediated pathways in the process of Familial Hypercholesterolemia.